The association of transcriptionally active genes with the nuclear matrix of the chicken oviduct. - Robinson, S I (1983)
Eucaryotic DNA is organized into a series of supercoiled loops that are anchored to the nuclear matrix. When these DNA loops are cleaved by endonucleases, the DNA sequences which remain associated with the nuclear matrix can be recovered and analyzed for their content of specific genes. Using restriction endonucleases to cleave the loops, we demonstrate that ovalbumin and conalbumin gene sequences are preferentially associated with the nuclear matrix of hen oviduct cells but not with the nuclear matrix of hen brain cells. Furthermore, we determined that several regions of the ovalbumin gene were independently attached to the nuclear matrix of hen oviduct cells. This included sequences located 3.8 kb downstream from the 3' end of the ovalbumin gene transcription unit. To determine whether the nuclear matrix association of the ovalbumin gene was regulated by hormones, we examined the oviduct cells of chicks that underwent primary estrogen stimulation, estrogen withdrawal and secondary estrogen stimulation. Ovalbumin gene sequences selectively dissociated from the chick oviduct nuclear matrix during estrogen withdrawal and reassociated with the nuclear matrix following restimulation.